ПОРІВНЯЛЬНА ХАРАКТЕРИСТИКА СТРУКТУРИ, ДІЯЛЬНОСТІ ТА ПРАВОВОГО СТАТУСУ КОМІТЕТУ РЕГІОНІВ (ЄВРОПЕЙСЬКИЙ СОЮЗ) І РАДИ РЕГІОНІВ (УКРАЇНА). ЕКОЛОГІЧНИЙ АСПЕКТ - Yanukovych, O.S. (Економіка та право, 2012)
In recent decades, the international community has pursued a targeted policy of eliminating the consequences of the ecological disaster. The experience shows the effectiveness of the government administration using a regional approach that is widely accepted in Europe. The paper shows the necessity of improving the regional governance (in particular, in the ecological sphere) taking into account the experience of the European Union.